Design A New Household Recycle Trash Bin - K., Kadirgama; M. M., Noor; M. R. M., Rejab; N. M. Zuki, N. M.; M. S. M., Sani (2008)

(untitled)
Recycling practices have become commonplace in household settings. Bottles, cans, and certain degradation materials such as chicken bones, fish bones and etc are commodities typically targeted. The paper presented the development of new concept of household recycle trash bin. Traditional trash cans still sit under or beside each household kitchen to be emptied by the nightly custodian. Discarded items with the exception of bottles, cans, and certain degradation materials end up in the trash can. Initially, the trash bin is drawn in SolidWork according to the design and finally fabricated it according to the final design. The heart of this recycle bin system is making people responsible for their trash by replacing each trash can with a recycle trash bin. The recycle trash bin can be a “saddle basket” placed on the side of the kitchen cabinet. In this system, people empty their recycle trash bins into centralized trash containers and their recycling bins into centralized recycling containers. Custodial workers no longer go house to house emptying trash cans. The unique of this recycle bin is a device attached together with it to compact the trash according to plastic bottles, aluminium cans and bones. After compact, people can easily place it inside centralized recycle bin according to the items. The degradation material can be used as a bio-fuel.